Contemporary and dynamic effects of socio-economic factors on physical (in)activity: Does intensity matter? - García-Witulski, Christian M. (Frontiers in Public Health, 2022)
Objective This paper identifies varying contemporary and dynamic effects of socio-economic factors on individuals' decisions to allocate their time to physical activities when the intensity of these activities comes into play. Methods Based on repeated cross-sectional data sourced from the Argentinean National Risk Factor Surveys of 2005, 2009, and 2013, we developed 18 fictitious cohorts to set up a pseudo panel. To address endogeneity problems, four econometric specifications were estimated: OLS, Heckman two-stage model, fixed- and random-effects models. Results We find that changes in the opportunity cost of time are highly significant and provide shifts in individuals' decisions regarding the allocation of their time to physical activity consumption. When considering the intensity at which physical activities are consumed, increased income impacts less, suggesting that individuals faced with a wage increase reduce the time of consumption but increase its intensity. An interesting finding is that employed people consume more physical activity than inactive individuals. This indicates that the substitution effect produced by an increase in the wage rate is less than the income effect. Additionally, the increase in the coefficient of employed persons is greater when the intensity factor is considered, indicating that for employed individuals a trade-off between time and intensity is generated. We also found that higher levels of education increase the probability of participating in physical activities, but decrease the time spent in such activities. Furthermore, there are heterogeneous impacts on physical activity consumption between males and females, which can be observed in the strong effect of household production for women with at least one child. Finally, such impacts remain in a variety of estimated specifications. Conclusions These results may be useful in order to suggest some tools for the design of interventions that are aimed at increasing participation in physical activities.